Self‐reported sensitivity to pain in early and moderately‐late preterm‐born adolescents: A community‐based cohort study. Issue 2 (11th May 2021) - van Dokkum, Nienke H.; de Kroon, Marlou L. A.; Reijneveld, Sijmen A.; Bos, Arend F.
Abstract: We aimed to compare ratings of self‐reported and parent‐reported pain sensitivity between early preterm (EP), moderately‐late preterm (MLP), and full‐term (FT) adolescents. For EP adolescents, we aimed to determine whether pain sensitivity was associated with early‐life events. EP (n = 68, response rate 47.4%), MLP (n = 128, response rate 33.0%), and FT (n = 78, response rate 31.1%) adolescents and their parents (n = 277) answered an author‐generated question on pain sensitivity at 14‐15 years of age within a community‐based cohort study. Differences between groups were determined using the chi‐square test for trends. For EP adolescents, we assessed associations of treatment modalities (inotrope treatment, mechanical ventilation, and C‐section) and neonatal morbidities (sepsis/necrotizing enterocolitis, small‐for‐gestational age status, asphyxia, and cerebral pathologies) with adolescent pain sensitivity using logistic regression analyses. Increased pain sensitivity was reported by 18% of EP adolescents, compared with 12% of MLP adolescents, and 7% of FT adolescents ( P = 0.033). Parent‐reported pain sensitivity did not differ by gestational age group. For EP adolescents, inotrope treatment was associated with increased pain sensitivity (odds ratio, 5.00, 95% confidence interval, 1.23‐20.4, P = 0.025). No other neonatal treatment modalities or morbidities were associated with pain sensitivity in adolescence. In conclusion, we observed higher proportions of increased pain sensitivity for EP and MLP adolescents. Physicians treating preterm adolescents should be aware of altered pain sensitivity.